Factors associated with post-traumatic stress syndrome in traffic accident victims served by the system SOAT - Percy Montesinos Valencia (2019)
The traffic accidents are a serious public health problem in Peru. They are the third overall mortality cause and the first among young adults. Traffic accidents are placed at the top of the list. Aside from causing injuries and the loss of man hours at work, these accidents bring about emotional distress to affected individuals.Our objective was to identify personal factors associated with the presence of PTSD in victims of traffic accidents attended by the SOAT system.For this, we devised this study is an observational cross-analytical prospective. The sample was chosen using selection criteria.The instrument used was the Davidson Trauma Scale, a psychometric instrument. Results from this study show some interesting characteristics from subjects involved in traffic accidents such as the fact that victims are mostly women with an elementary education level and without a partner by the time of the accident. Falls from vehicles, people run over by cars and individuals driving alone at the time of accidents were other relevant high-impact findings.A higher rate of post-traumatic stress disorder was reported in individuals who suffered an accident while being inside a vehicle, in individuals involved in an accident which had occurred between one and three months before and who in addition tended to present a negative affect profile.We conclude that older patents, female sex, low instruction and dependent occupation, and also brain trauma and sequels by the accident are related to the presence of post-traumatic stress disorder.